Radiogenic risk of solid cancer incidence in persons exposed to radiation in childhood in the Southern Urals - L. Yu. Krestinina; S. A. Shalaginov; S. S. Silkin; S. B. Epifanova; A. V. Akleyev (Радиационная гигиена, 2021)
The aim of this work is to assess the radiogenic risk of solid cancers incidence in the members of the Urals Childhood Exposure Cohort. The cohort includes people exposed under 20 years of age as a result of two radiation accidents at the Mayak Production Association in the Southern Urals (discharges of radioactive waste into the Techa River and the formation of the East Ural radioactive trace). The number of the cohort for solid cancer incidence analysis is 31,578 individuals. All the members were postnatally exposed and some of them – in-utero. Some of their parents were exposed before conception. 2,018 solid cancers were registered on the incidence catchment area during the period 1956-2018, the total amount of person years was 818,083. The analysis was carried out by the Poisson regression method with a simple parametric excess relative risk model. 95% confidence intervals were estimated with maximum likelihood approach. Only a postnatal dose was used in the first solid cancer incidence analysis of this cohort members with due account for preconception exposure of parents. TRDS-2016 mean postnatal dose accumulated over the entire follow-up period in the stomach of cohort members was 0.047 Gy. The analysis showed linear dependence of solid cancer incidence excess relative risk on postnatal dose. Excess relative risk was 0.66/Gy, р=0.006 with a five-year latency period. While estimating excess relative risk in different age groups at the beginning of exposure, a significant risk was present only in the age group under 1 year and amounted to 2.16/Gy; р<0.02 at the onset of exposure. The present results are in agreement with the results of the solid cancer incidence risk analysis both in the Techa River Cohort of exposed In-Utero where a statistically significant excess relative risk from a postnatal dose was revealed, and with the results of risk analysis in the Japanese cohort of people exposed in-utero and in early childhood.